(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The concept of self-healing based on characteristics of environment design of surrounding the individual ,Healing by design, one of the most important concepts corresponding to the healing environment or healing in the context of healthcare buildings, where the awareness of this concept reach on the characteristics of internal environment in general to make it more healthy, stimulating and vital, the concept of self-healing is result of analyzing the mutual and vital relationship between human and physical and natural environment in an attempt to understand the relationship and the extent of its repercussions on the physiological and psychological level of the individual. The process of healing cannot be understood by isolation from the factors that work dynamically in the life of individual ,and function of the building is not limited to housing and containment of activities and to meet functions of life, but the most important role is to improve the performance of vital act of life and make it healthy and support self-healing. Hence, the problem of research in the awareness of importance of architecture in taking the task of stimulating self-healing for the individual, and identify characteristics of design approach based on the design processes resulting from the dynamic relationship of the individual’s living with the environment. The object of the study is to build a theoretical framework of design recruitment strategies in the process of self-healing of individuals Both for therapeutic environment and general internal environment, and to derive the possible values ​​of the design characteristics that achieve those strategies stemming from the mechanism of involving the individual in a conscious and clear process of support, balance and moral nutrition in relation to the environment. The basic and secondary vocabulary and possible values ​​of the conceptual framework for the strategies of design recruitment in the healing process were three basic strategies: strategy of environment potential supporting of individual, strategy of balancing the life components of the individual and experiment of space transition, and finally the nutrition strategy at the vital and poetic level of individuals. The conclusions were based on objective understanding of the quality of design that supports the process of healing, which is completely different from the concept of design in dealing with static and formal assets. The design here is characterized by the dynamic nature of healthy lifestyle design based on stimulating the process of healing at organic, sensory and moral levels for individuals.